Whose hand on the wheel ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The way to higher yields is through irrigation, some experts say. Others claim it lies in more efficient rainfed agriculture. After all, irrigation is a thirsty consumer. As a general rule it takes 1000 litres of water to produce 1 kg of food. Water...